2014
DOI: 10.1073/pnas.1411260111
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the dynamic genome: Steroids, epigenetics, and the transposome

Abstract: Stress plays a substantial role in shaping behavior and brain function, often with lasting effects. How these lasting effects occur in the context of a fixed postmitotic neuronal genome has been an enduring question for the field. Synaptic plasticity and neurogenesis have provided some of the answers to this question, and more recently epigenetic mechanisms have come to the fore. The exploration of epigenetic mechanisms recently led us to discover that a single acute stress can regulate the expression of retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 112 publications
(129 reference statements)
0
80
0
3
Order By: Relevance
“…This repression is lost with repeated stress, suggesting the possibility that those retrotransposon elements may impair genomic stability under conditions of chronic stress (Hunter et al, 2015).…”
Section: Epigenetics Stress and Mood-related Behaviors: Search For mentioning
confidence: 99%
“…This repression is lost with repeated stress, suggesting the possibility that those retrotransposon elements may impair genomic stability under conditions of chronic stress (Hunter et al, 2015).…”
Section: Epigenetics Stress and Mood-related Behaviors: Search For mentioning
confidence: 99%
“…These differences in chromatin remodeling in rats exposed to acute versus chronic intermittent restraint may be related in part to habituation of the HPA axis to chronic intermittent restraint stress. In an extension of their work, Hunter et al (2015) considered the ways in which exposure to stress could produce persistent alterations in neural and endocrine responses and behavior. They suggested that expression of retrotransposons may play a critical role in stabilizing genomic activity in stress-sensitive brain regions such as the hippocampus…”
Section: Neural Adaptations To Stress: Role Of Transcriptional Changesmentioning
confidence: 99%
“…In recent years, numerous studies in both human MDD and in animal models of depression have identified changes in gene expression, along with related alterations in chromatin structure and function, that contribute to aberrant forms of transcriptional and behavioral plasticity associated with depressive-like phenotypes (4)(5)(6)(7)(8)(9). Although multiple studies have successfully linked alterations in histone posttranslational modifications (PTMs) or chromatinremodeling events to chronic stress susceptibility or resilience (e.g., using a model of chronic social defeat stress-CSDS-an etiologically valid rodent model of human depression), the precise histone regulatory phenomena involved in stress-mediated behavioral responses remain poorly understood.…”
mentioning
confidence: 99%